A Case Series of 13 Patients with COVID-19 Associated Respiratory Symptoms Treated with Nebulized OTR4120 (Cacipliq20®) - Ali, El Husseini; Denis, Barritault (Archives of Clinical and Medical Case Reports, 2022)
We report a series of 13 patients with COVID-19 treated with Cacipliq20®, an heparan sulfate mimetic approved for the treatment of hard to heal cutaneous ulcers. Heparan sulfates play important roles in tissue repair and possess antiviral activity. Cacipliq20® was administered through nebulization at a dose of 45 μg twice a day for 5.5 consecutive days. All patients presented respiratory symptoms with some dyspnea and in most cases pulmonary abnormalities on chest CT-Scan. Eight patients presented with a moderate form of the disease, three patients with a severe form, one with a mild form, and one with a critical form. In all patients the treatment was added to the standard of care. Ten patients were treated during the acute stage of the disease (<4 weeks from symptoms onset) while 3 patients were in the postacute stage (>4 weeks from symptoms onset). A second treatment was administered for another 5.5 days in 6 patients. All patients showed clinically improvement after treatment. The time to first improvement ranged from 2 to 4 days after first treatment onset with a median of 3 days. Time to full clinical recovery ranged between 6 to 27 days from treatment onset with a median of 6 days. Lung CT scans followed clinical impression and showed a clear improvement of the lesions in most cases. The treatment was well tolerated in all patients. These preliminary observations should justify further evaluation through a well-designed placebo-controlled therapeutic trial.